Serum Neopterin Levels Among Hepatitis C-Positive Living-Donor Renal Transplant Recipients - Justa, Shivali (Biomark Insights, 2015)
BACKGROUND: The role of neopterin as a marker of cell-mediated immunity for immunological monitoring after transplantation is of great potential interest. Neopterin levels among hepatitis C virus (HCV)-positive recipients of living-donor renal transplantation (LDRT) have not been previously described. METHODS: Twenty-two HCV-positive (group I) and 10 HCV-negative (group II) recipients of LDRT were serially monitored for serum neopterin levels by enzyme-linked immunosorbent assay (ELISA). Group I patients were monitored thrice, ie, before transplantation, day 10, and 6 months post transplantation, while group II patients were monitored twice (day 10 and 6 months post transplantation). Peripheral blood T-lymphocyte subsets (CD3, CD4, CD8, CD4(+)CD25(+), CD(16+56)) and Th1/Th2 cytokines were monitored concomitantly by flow cytometry. RESULTS: Ten days post transplantation, there was a significant increase in neopterin and neopterin/creatnine levels among group I patients. There was a positive correlation between activated T-lymphocyte (CD4(+)CD25(+)) and neopterin early post transplantation (day 10). Th2 cytokines IL-10 and IL-5 showed a positive correlation with neopterin levels on day 10 and 6 months post transplantation, respectively. Neopterin levels did not show association with either HCV viral load or allograft rejection among our study cohort. CONCLUSION: Increased monocyte/macrophage activation with elevated serum neopterin was detected among group I patients on day 10 post transplantation, but it could not predict rejection. It appears that IL-10 either from a regulatory or nonregulatory source helps in the maintenance of stable graft early post transplantation. Further, it would be of interest to assess the role of neopterin in chronic allograft nephropathy and long-term graft outcome.